A influência do índice de desenvolvimento humano na hospitalização e mortalidade do câncer de colo de útero no Brasil. - de Souza Borges, Cintia; Casagrande, Sabrina; Souza Kock, Kelser (Enfermagem Brasil, 2025)
Introduction: Cervical cancer (CC), also known as cervical carcinoma, is considered a public health issue, especially in less developed countries where prevention and treatment resources are scarce. Objective: This study aimed to describe and compare hospitalization and mortality due to cervical cancer across Brazilian states, correlating these data with the Human Development Index (HDI) of each state from 2010 to 2020. Methods: This is an ecological study that analyzed cases of hospitalization and mortality due to cervical cancer in each Brazilian state between 2010 and 2020, using data from DATASUS. Additionally, the HDI of each state was obtained from the Atlas of Human Development in Brazil. Results: Between 2010 and 2020, there were 239.716 hospitalizations and 63.990 deaths from cervical cancer in Brazil. The country showed a decrease of 0.29 hospitalizations per 100.000 inhabitants per year and an increase in mortality, with a rise of 0.12 deaths per 100.000 inhabitants per year. Moreover, states with higher HDI had higher hospitalization rates, whereas states with lower HDI had higher mortality rates. In addition, it was found that the higher the HDI of the state, the higher its hospitalization rate. On the other hand, the lower the HDI, the higher the mortality rate. Conclusion: Although there was a decrease in hospitalization for cervical cancer in recent years, mortality has increased. Furthermore, states with lower HDI levels presented higher mortality rates. It is of utmost importance to expand access for women to necessary screening exams for the early diagnosis of pre-neoplastic lesions and cervical cancer.